How Gylfi’s Illusion Breathes Life into the Sky - Gísli Sigurðsson (Religionsvidenskabeligt tidsskrift, 2022)
ABSTRACT: To date it has mostly been overlooked that the illusion in ‘Gylfi's Illusion’ is based on a metaphor, where what we can literally see in the sky is transformed into mythological phenomena through the magic of storytelling. By taking this idea at face value it becomes possible to look at the sky as a memory tool for the world of the gods. Thus everything we have above us in the sky has a mythological name and often a story attached to it, making it easier to remember all the details of the mythology as well as knowing your way around the sky. This approach to the mythology of Gylfaginning puts us on firm ground as we read it for what it is: a reflection of contemporary and traditional terminology about the sky as it was known to northern peoples from long before Christianity.